2007
DOI: 10.1097/jsa.0b013e3181595c39
|View full text |Cite
|
Sign up to set email alerts
|

Superior Labral Repair

Abstract: Advances in shoulder arthroscopy have led to a greater understanding of the importance of lesions of the superior labrum and biceps tendon complex. Diagnosis of superior labrum anterior to posterior tears requires a high index of suspicion and is made by careful attention to the history, physical examination, and magnetic resonance arthrography. The diagnosis is confirmed with arthroscopy. The form of treatment is dependent on the type of tear and the stability of the superior labrum and biceps anchor. Appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…8 We know through previous anatomic studies that the suprascapular nerve and its branches track close to the glenoid rim; some research has shown this distance to be quite short, with a mean distance of 20 mm. 1,2,15 However, little research has been conducted into the risk of neurovascular injury from the ''blind'' drilling, that is, drilling where the surgeon is unable to directly visualize the drill path to create holes for the placement of suture anchors.…”
mentioning
confidence: 98%
“…8 We know through previous anatomic studies that the suprascapular nerve and its branches track close to the glenoid rim; some research has shown this distance to be quite short, with a mean distance of 20 mm. 1,2,15 However, little research has been conducted into the risk of neurovascular injury from the ''blind'' drilling, that is, drilling where the surgeon is unable to directly visualize the drill path to create holes for the placement of suture anchors.…”
mentioning
confidence: 98%
“…In patients undergoing repair, some authors advocate the use of two anchors, one anterior and one posterior to the biceps anchor, whereas others advocate a single double-loaded anchor, with sutures passed in a similar fashion. Alternatively, many advocate a single point of fixation posterior to the biceps anchor 25,56,57 . For posterior lesions, a shift to an anterior viewing portal and deployment of the shaver via the posterior portal may assist with debridement 57 .…”
Section: The Superior Labrum Anterior and Posteriormentioning
confidence: 99%
“…Alternatively, many advocate a single point of fixation posterior to the biceps anchor 25,56,57 . For posterior lesions, a shift to an anterior viewing portal and deployment of the shaver via the posterior portal may assist with debridement 57 . Suture anchors are placed at the superior glenoid articular cartilage margin at a 45°angle for maximum anchor security.…”
Section: The Superior Labrum Anterior and Posteriormentioning
confidence: 99%
See 1 more Smart Citation
“…11) (20, 78, 81, 103, 109). Differentiating this type of injury from labral detachments may imply changes in the surgical technique (109). However, the imaging differentiation between these lesions can be difficult.…”
Section: Imaging Findingsmentioning
confidence: 99%